2003
DOI: 10.1038/sj.bjc.6601165
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in tumour necrosis factor (TNF) are associated with risk of bladder cancer and grade of tumour at presentation

Abstract: The purpose of this study is to assess the role of tumour necrosis factor (TNF) polymorphisms in the risk of developing bladder cancer and effect on tumour stage, grade and progression. In all, seven single-nucleotide polymorphisms in TNF were studied in 196 bladder cancer patients and 208 controls using a PCR-SSP genotyping technique. It was seen that there was a significant association of two polymorphisms in TNF with bladder cancer: the TNF þ 488A allele was found in 28.1% of patients compared with 14.9% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…In bladder cancer, Inatomi et al (1999) showed that bladder cancer patients with NAT2 slow genotypes were more likely to have a high-grade tumor (G3) or an advanced stage tumor (pT2-pT4). Also, significant associations between TNF polymorphisms TNF þ 488A and TNFÀ859T and grade of bladder cancer were observed (Marsh et al, 2003).…”
Section: Genetic Polymorphisms In Natural History Of Diseasementioning
confidence: 99%
“…In bladder cancer, Inatomi et al (1999) showed that bladder cancer patients with NAT2 slow genotypes were more likely to have a high-grade tumor (G3) or an advanced stage tumor (pT2-pT4). Also, significant associations between TNF polymorphisms TNF þ 488A and TNFÀ859T and grade of bladder cancer were observed (Marsh et al, 2003).…”
Section: Genetic Polymorphisms In Natural History Of Diseasementioning
confidence: 99%
“…Commonly described variants of TNF-α gene polymorphisms consist of G to A transitions in the promoter region at positions _238 and _308 (Kaluza et al, 2000). So far, TNF-α promoter polymorphism has been related to numerous cancers, such as bladder cancer (Marsh et al, 2003), renal cell carcinoma (Nakajima et al, 2001), non-small cell lung carcinoma (Shih et al, 2006) cervical cancer (Govan et al, 2006;Liu et al, 2012b) and breast carcinoma (Mestiri et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Bladder cancer patients carrying the A allele seem to have increased TNF-␣ in serum and tumor tissue [43] . Although the TNF-308G/A polymorphism was described as being associated with grade, much debate still exists concerning its association with stage and other clinicopathological characteristics [43,44] .…”
mentioning
confidence: 99%